Comment on: Red blood cell distribution width as a surrogate biomarker of damage and disease activity in patients with systemic lupus erythematosus - Moreno-Torres, Víctor; Castejón Díaz, Raquel (Clinical and experimental rheumatology, 2025)
[Resumen no disponible]
Keywords: comment; red blood cell distribution width; surrogate biomarker of damage; disease activity; systemic lupus erythematosus